2018
DOI: 10.17533/udea.iee.v36n2e05
|View full text |Cite
|
Sign up to set email alerts
|

Rapid response team: what factors interfere with its performance

Abstract: Objective. Describe the knowledge in the literature related to factors that influence the performance of response teams. Methods. Integrative review of the literature of articles published in Portuguese, English or Spanish between 2006 and 2016. The descriptors hospital rapid response equipment, cardiac arrest and hospital mortality were used for the search in the PubMed/ Medline, Lilacs -Bireme and CINAHL bibliographic databases. Results. 19 studies were included for the analysis. The results were categorized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 31 publications
0
10
0
3
Order By: Relevance
“…To our knowledge, our study is the first to reveal that FiO 2 , which was not included in the RRT call criteria, was related to the progression of clinical deterioration. Several studies have shown an association between delayed RRS activation and increased in-hospital mortality rates, length of hospital stay, and number of cardiorespiratory arrests, as well as high ICU admission rates [23][24][25][26][27]. Prompt RRS activation is warranted in patients who require RRT intervention.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, our study is the first to reveal that FiO 2 , which was not included in the RRT call criteria, was related to the progression of clinical deterioration. Several studies have shown an association between delayed RRS activation and increased in-hospital mortality rates, length of hospital stay, and number of cardiorespiratory arrests, as well as high ICU admission rates [23][24][25][26][27]. Prompt RRS activation is warranted in patients who require RRT intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, improper prioritisation of RRS-activation barriers such as calling the doctor, consulting a colleague, or continuing observation, over timely RRS-activation causes prolongation of afferent limb (Wood et al, 2019), and thus, a delay in RRS-activation. Of note, any delay in RRS-activation is associated with adverse outcomes (Reardon et al, 2018), such as in-hospital cardiac arrest and cardiovascular dysfunction, unplanned ICU admissions, mortality, and hospital length of stay (Kollef et al, 2017;Lee et al, 2018;Moreira et al, 2018;Reardon et al, 2018;Tirkkonen et al, 2013;Xu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Failure to recognise and respond to deterioration could be attributed to several RRS-activation barriers, such as interaction between nurses and RRS team, physician influence, hospital culture, nurse experience, and nurse education (Padilla et al, 2018;Wood et al, 2019). The RRS barriers are especially very important because a delay or failure in an afferent limb results in adverse outcomes for patients (Lee et al, 2018;Moreira et al, 2018;Reardon et al, 2018;Xu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Con este propósito fue creado el equipo de respuesta rápida 52,53,172,173 , promovido por el Instituto de Mejora en el Cuidado de la Salud (Institute for Healthcare Improvement) en la campaña «Salvar 100,000 vidas» como una de las seis intervenciones claves para mejorar la calidad del cuidado hospitalario 174,175 . El equipo de respuesta rápida es multidisciplinario, variando su constitución según país e institución 52,178,[190][191][192] .…”
Section: Vigilancia Y Prevenciónunclassified